Assessment of Attitude towards two selected areas of professionalism like honesty and confidentiality among undergraduate medical students of Bangladesh - Khan, Sadia Jabeen; Talukder, Md Humayun Kabir; Alam, Kazi Khairul; Haque, Farhana; Karim, Md Rezaul (Bangladesh Journal of Medical Education, 2020)
This descriptive type of cross sectional study was carried out to evaluate the attitude of undergraduate medical students of Bangladesh regarding selected areas of professionalism like honesty and confidentiality. Study period was from July 2017 to June 2018. Sample size was 837 undergraduates medical students of 1st, 2nd, 3rd and 4th phase of MBBS course from four public and four non government medical colleges of Bangladesh. Convenience sampling technique was adopted in this study. Data collection was done by a modified structured situational judgment test (SJT) self-administered questionnaire which was adopted from general medical council (GMC) and by in-depth interview schedule of students. The data were then compiled and analyzed using SPSS Version 19.Among the study participants, 37.20% (310) and 62 .80% (537) were males and females respectively. Attitude towards the two most major issues of professionalism were good, mean score were above three in honesty. Mean score was below three in maintaining confidentiality. Result of the present study shows that female students had higher mean professionalism than male. Female students were better than the male students in regards to all two different professional issues and this difference is statistically highly significant (P=0.00). Mean score of professionalism of 1st phase students in all two issues were greater than the respondents of other three phases and this findings was also statistically significant. Medical undergraduates of Bangladesh have a good understanding of acceptable professional honesty but there is scope of improvement. Study recommended that these two issues of professionalism must be taught in the course of undergraduate medical education and should be incorporated in undergraduate medical curriculum with the details of learning outcome what we craving from a registered medical graduate so that learning can be turned into practice. Bangladesh Journal of Medical Education Vol.11(1) 2020: 3-11